2019
DOI: 10.3389/fpsyg.2019.02480
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Relationship Between Gratitude and Life Satisfaction: Evidence From Two Longitudinal Field Studies

Abstract: Gratitude and life satisfaction are associated with several indicators of a good life (e.g., health, pro-social behavior, and relationships). However, how gratitude and life satisfaction relate to each other over time has remained unknown until now. Although a substantial body of research has tested the link from gratitude to life satisfaction, the reverse association remains unexplored. In addition, recent cross-cultural research has questioned the link between gratitude and subjective well-being in non-Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 77 publications
2
29
0
Order By: Relevance
“…For instance, Vittersø and Søholt (2011) showed that life satisfaction predicted feelings of pleasantness (a composite index of contentment, enjoyment and happiness) among young adults (aged between 18 and 31) in Norway. Relatedly, Unanue and his colleagues (Unanue et al, 2019) found that people who were more satisfied with their lives were more likely to appreciate the positive in life and, in particular, to feel a strong sense of gratitude.…”
Section: Life Satisfaction and Outgroup Attitudesmentioning
confidence: 97%
“…For instance, Vittersø and Søholt (2011) showed that life satisfaction predicted feelings of pleasantness (a composite index of contentment, enjoyment and happiness) among young adults (aged between 18 and 31) in Norway. Relatedly, Unanue and his colleagues (Unanue et al, 2019) found that people who were more satisfied with their lives were more likely to appreciate the positive in life and, in particular, to feel a strong sense of gratitude.…”
Section: Life Satisfaction and Outgroup Attitudesmentioning
confidence: 97%
“…Research has found that gratitude relates to several indicators of well-being such as higher life satisfaction, positive affect/emotions, autonomy, competence, relationships, optimism, prosocial behaviour, and personal growth. Gratitude also relates to a multiplicity of indicators of ill-being such as lower negative affect/emotions, depression, anxiety, anger, and hostility [ 13 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there exist an evidence of gratitude contributing in development of emotional intelligence and life contentment (Geng, 2018;Unanue et al, 2019 8. Females have higher degree of depression, anxiety, and stress than males.…”
Section: Significancementioning
confidence: 99%
“…It has a positive relationship with transpersonal gratitude which is found to foster life contentment and also act as the precursor of it (Salvador-Ferrer, 2017; Unanue et al, 2019).…”
Section: Introductionmentioning
confidence: 99%